The Effects of Inflation, BI 7-Day Repo Rate, and Dollar Exchange Rate on the Jakarta Composite Index (JCI) in Indonesia - doniyusufbagaskara; rohmadi (Journal of Economic and Business Analysis, 2023)
This study aims to determine the effect of Inflation, BI 7-Day Repo Rate, and Dollar Exchange Rate on the Composite Stock Price Index (JCI) in Indonesia. This study uses quantitative methods, the study population uses monthly data in 2018 – 2022 in Indonesia, this study uses a sample collection technique model with non-probability sampling or non-random samples. Data sources come from data and documents from the Central Statistics Agency (BPS), Bank Indonesia (BI) and the Ministry of Trade of the Republic of Indonesia. The analysis process uses multiple regression analysis of time series data assisted by SPSS 2023. The results of this study stated that inflation had a significant positive effect on JCI, while the BI 7-Day Repo Rate had a negative effect on JCI, and the Dollat Rate had no effect on JCI.